Cyathea sunduei, a new name for a recently described Colombian tree fern (Cyatheaceae) - Lehnert, Marcus (Phytotaxa, 2017)
In a recent publication describing three new tree ferns for Colombia, Rojas & Tejedor (2016) regrettably chose an epithet that was already taken. For this species, a new name is chosen herewith: Cyathea sunduei Lehnert, nom. nov. for Cyathea incognita A.Rojas in Rojas & Tejedor.